(untitled) (Innovative Technologica: Methodical Research Journal, 2022)
The problem of iodine deficiency is extremely important and relevant for many countries. More than 1 billion inhabitants of the earth live in places with a low content of iodine in the biosphere (water, soil, air, food). As a result of this deficiency, 200 million people develop an enlarged thyroid gland (endemic goiter), 20 million develop mental retardation due to insufficient thyroid hormones. It has been established that the high prevalence of endemic goiter among schoolchildren leads to a decrease in cognitive abilities by 15 percent.